Treatment of a bilaterally severely resorbed posterior mandible due to early tooth loss by Guided Bone Regeneration using customized allogeneic bone blocks: A case report with 24 months follow‐up data. Issue 6 (19th June 2018) - Blume, Oliver; Back, Michael; Born, Teresa; Smeets, Ralf; Jung, Ole; Barbeck, Mike
Abstract: Objective: The use of allogeneic bone grafts for alveolar ridge reconstruction has become an often‐discussed alternative to augmentation procedures using autografts. Nevertheless, there still is a lack of literature concerning long‐time experiences of allografts for alveolar ridge reconstruction. Especially the results of the use of allogeneic bone blocks for mandible reconstructions need to be further investigated. Clinical Considerations: In this case report, we present the use of customized allogenic bone blocks in Guided Bone Regeneration (GBR) procedures for severely deficient mandibulary bones, the implantation after a healing period of 5 month and the 24‐month follow‐up data. Conclusions: Customized allogeneic bone blocks seem to be a successful alternative to augmentations with autologous bone blocks reconstructing highly resorbed mandibulary alveolar ridges, showing highest volume stability and no signs of bone resorption after implant loading. Clinical Significance: The application of customized allogeneic bone blocks has shown to be a successful augmentation technique even compared with with autologous bone blocks reconstructing highly resorbed mandibulary alveolar ridges demonstrating no compromises regarding clinical outcome, functionality and esthetics.